KEEFEKTIFAN STRATEGI METAKOGNITIF BERBANTU ADVANCE ORGANIZER UNTUK MENINGKATKAN HASIL BELAJAR KIMIA SISWA - Namira, Zara Bunga; Kusumo, Ersanghono; Prasetya, Agung Tri (Universitas Negeri Semarang, 2014)
This study aims to determine the effectiveness of the use of learning methods with metacognitive strategies assisted Advance Organizer. Research design used was a pretest posttest control group. The effectiveness of the research will be presented with the classical student learning completeness minimum 85%. The study population was all students of class X in a school of Tengaran. Samples were X-5 class (the experimental class) and X-4 (grade control) were taken with a cluster random sampling technique. Experimental class implements metakogntif assisted learning strategies Advance Organizer while the control class is not apply metacognitive strategies assisted Advance Organizer. The research instrument used is the observation sheet affective and psychomotor, cognitive and achievement test sheet student questionnaire responses. The data were taken from learning outcomes and student response. Based on data analysis, it obtained that the average student learning outcomes for experimental class was 78.32, and control class was 75.09, with classical cognitive mastery ofÂ learning outcomes for experimental class was 88.23% and control class was 70.59%. The average of experimental class students have a good response on learning that used metacognitive strategies assisted Advance Organizer. It can be concluded that metacognitive strategies assisted Advance Organizer effectively can improve the student learning outcomes in school.Keywords: Advance Organizer, Learning Outcomes, Strategy Metacognitive